RESEPSI DIALEKTIKA HUKUM ISLAM DENGAN BUDAYA (STUDI ATAS PRAKTEK PEMBAGIAN HARTA WARISAN MASYARAKAT BUMIHARJO DAN SELOMARTO GIRIWOYO WONOGIRI) - Diana Zuhroh; Lila Pangestu Hadiningrum; Andi Cahyono (Mahkamah : Jurnal Kajian Hukum Islam, 2020)
This study aims to describe the practice of the distribution of inheritance in the villages of Bumiharjo and Selomarto Giriwoyo Wonogiri, assess the views and relevance of Islamic law in the practice of inheritance distribution in Selomarto and Bumiharjo villages and describe the relevance of the objective conditions of the tradition of inheritance distribution in the villages of Bumiharjo and Selomarto with the law his family. This research is a qualitative field study using a sociological normative approach. Data analysis using the Miles-Huberman model includes data collection, data reduction, data display and conclusion drawing. From the data in the field, it was found that the practice of distributing inheritance to the people of Bumiharjo Village and Selomarto Giriwoyo Wonogiri was carried out while the heir was still alive and after he died. While the practice of dividing the inheritance after the testator dies is carried out by means of gantungan or delays. In certain cases, where girls are mokok’i keprabon, then their share is greater than boys. The practice of dividing inheritance with lintiran is identical to a grant, while the practice of cungan is identical to a will. The practice of segendong sepikul is relevant to the provisions of Islamic inheritance law where men get a double share of the women's share. The practice of dividing inheritance equally between men and women is less relevant to the understanding and practice of family law in Bumiharjo and Selomarto communities where men are responsible for family livelihoods.